2008
DOI: 10.4162/nrp.2008.2.3.184
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient intake and bone health status of Korean male college students as related to smoking situations

Abstract: The purpose of this study was to compare the dietary habits, nutrient intake, bone mineral density (BMD) and bone metabolism in Korean male collegians as related to smoking situation. One hundred sixty one young adult males at the age of 20-26 participated in this study. The subjects were divided into four groups: non smoker (n=42), light smoker (n=34), moderate smoker (n=49) and heavy smoker (n=36). The anthropometric characteristics, smoking situations, dietary habits and nutrient intakes were observed. Bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Another limitation of the present study was the lack of information on iron intake in the study population. Low intakes of iron have been reported among young smokers in Korea [24]. The difference in serum levels of iron between smoke resistant and non-resistant subjects may be attributable to differences in daily intake of iron from food.…”
Section: Discussionmentioning
confidence: 95%
“…Another limitation of the present study was the lack of information on iron intake in the study population. Low intakes of iron have been reported among young smokers in Korea [24]. The difference in serum levels of iron between smoke resistant and non-resistant subjects may be attributable to differences in daily intake of iron from food.…”
Section: Discussionmentioning
confidence: 95%
“…An imbalanced diet may be one of the reasons for the low health-related quality of life in smokers (24). Also, Korean male smokers consumed less calcium but more coffee and alcohol, which is obviously detrimental to their bone health (9). There is even a theory suggesting that caffeinated or alcoholic beverages may enhance the taste of smoking (10).…”
Section: Discussionmentioning
confidence: 99%
“…Previous Korean studies on the nutrient intake of smokers were only sporadically reported, and most subjects were too small or too focused on specific groups (9, 10). Therefore, further study on the nutrient intake and dietary pattern of smokers should broaden its approach to consider a nationally representative sample.…”
Section: Introductionmentioning
confidence: 99%
“…For example, milk intake (or calcium intake from any source), one of the most import confounding factors, was adjusted in only four included studies. Smoking is also known to be associated with coffee consumption [38], and evidence showed that of all hip fractures, one in eight was attributable to smoking [46]. But not all original data extracted have been adjusted for it.…”
Section: Discussionmentioning
confidence: 99%